Estudio de mercado para la creación de una guardería, en beneficio de los estudiantes y servidores de la Universidad Técnica Estatal de Quevedo - Terán Saltos, Rosa Elena (2011)
This research was developed in the State Technical University located at kilometer Quevedo ½ way to Sto. Domingo and his purpose was to conduct a market study for the creation of a kindergarten in UTEQ. to determine the degree of acceptance of childcare for the benefit of students and server service that is not available within the campuses. The above aspects have been allowed to consider as an excellent idea, the creation of a crèche, UTEQ due to the situation of mothers who have ties with the university as students and servants who have no one to delegate the care of their children. The results obtained in field work and the interviews give a sample of 354 people including students, UTEQ servers from a population of approximately 4595 college players, led to a positive outcome to a day care facility. The methodology was oriented routing in field research, literature, qualitative and quantitative that used direct observation techniques and a structured assessment tool was used in the survey. Once the market study it was determined that the service will provide the daily care of children from 3 months to 7 years old, with innovative approaches to intellectual and psychomotor development will target the children of students and UTEQ servers. It should be noted that respondents concerned about the welfare of their children felt right to have the service of a medical professional, classes also include physical education and art, it follows that the people involved that their infants are interested in receiving a good deal, also chose to receive transportation services to include a refund of that month, with attention Monday to Friday from 08h00 to 18h00 without ignoring the opinion of other options for how to set schedules that satisfy all potential users. For this study we proceeded to visit the nurseries of competition: Baby Gym, Trampoline and the Child Development Center and through a dialogue with their managers were known services offered by these establishments such as monthly fees, hours of operation, number of children they have, and so on. Demand is supported by the results of encuestas monthly and annually. As for the name of the business it was created for the purpose that you mention are easily know the type of service offered, which projects seriously and let stand, and generates recall because the way they name the business determined many cases the first impression you convey to the stakeholders, the design of the logo is to draw attention of our potential customers, visitors, and to convey clearly that is dedicated to the company, the slogan will be used to project in a simple brief, which provides business and how it differs from its competitors, this was created as a proposal for the creation of the nursery. In this context the daycare could be the quality of self-management and allow children to have a supportive environment that helps the affective, psychomotor and cognitive and practical teaching of values.